Influence of Aluminum Mesh electrode on Performance of a Microbial Fuel Cell (MFC) - M.I.N, Ma'arof; Chala, Girma T.; Saravanan, Ravichanthiran (Science Publishing Corporation, 2018)
Recently, various steps have been taken to utilize and develop renewable and sustainable form of energies due to the negative impact and dire limitation over continuous dependency on fossil fuel. This paper presents the effects of aluminium mesh on the performance of a MFC. Aluminium mesh with rectangular shape was used as the electrode and experiments were conducted with respect to various types of resistors. The amount of voltages and power density generated were determined. It was found that the increase in bacterial activities resulted in the increment of oxygen supply, therefore, the voltage generated also increased. In addition, the longevity of bacterial activity is dependent on the amount of catalyst. Moreover, it was observed that the performance of aluminium mesh electrode was smaller than that of graphite electrode.